Working with gender and sexual minorities in the context of Islamic culture: a queer Muslim behavioural approach. (1st April 2019) - Farhadi Langroudi, Khashayar; Skinta, Matthew D.
Abstract: There has been a large increase in the migration of Muslim populations towards the western world and the USA in the past decade. Many have migrated in the hope of finding a safe home away from war, persecution, or a better economic situation, with many coming from Afghanistan and Syria. Gender and sexual minorities (GSM), or individuals who are not heterosexual and do not identify with their sex assigned at birth, are disproportionately over-represented within migrating groups. While most of these individuals will not have received psychotherapy in their home countries, it is likely they would receive or be required to obtain psychological services as part of the asylum process or through psychoeducational services as a requirement to receive assistance. In exploring the specific needs of Muslim GSM individuals, we highlight the diverse impacts of minority stress, shame, and how these might be mitigated through the integration of acceptance and commitment therapy (ACT) and compassion-focused therapy (CFT). ACT and CFT may provide a helpful framework for a culturally adapted therapy that targets the needs of those experiencing intersectional Muslim and GSM identities, and can foster the cultivation of a meaningful life that can include all aspects of their identities. Key learning aims: (1) To understand the context within which Muslim GSM individuals experience shame. (2) To learn to adapt an acceptance and compassion-based approach in working with GSM Muslim clients. (3) To describe how culturally competent hypotheses might inform case conceptualization with GSM Muslim clients.